The 'Pinocchio' nasal deformity due to cavernous lymphangioma. - Hobby, J L (1995)
The 'Pinocchio' or 'Cyrano' nose is a rare condition in which deformity of the nasal tip is produced by an underlying soft tissue tumour. Previously reported cases have been due to either capillary or cavernous haemangiomas (angiolipomas). The deformity is the cause of much teasing in children. There has been debate as to whether surgical intervention is indicated, as a proportion of cases will regress spontaneously. We report a case of 'Pinocchio' nose with a lymphangioma of the nasal tip which is previously undescribed and review the options for management.